2015
DOI: 10.1136/bjophthalmol-2015-307871
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic autorefraction versus subjective refraction: the Tehran Eye Study

Abstract: The cycloplegic refraction is more sensitive than the subjective one to measure refractive error at all age groups especially in children and young adults. The cyclorefraction technique is highly recommended to exactly measure the refractive error in momentous conditions such as refractive surgery, epidemiological researches and amblyopia therapy, especially in hypermetropic eyes and paediatric cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 18 publications
1
69
0
2
Order By: Relevance
“…Overall, cylinder values with autorefraction are significantly overestimated compared with retinoscopy. In a similar comparative study of cycloplegic values using retinoscopy and autorefraction, cylinder values showed a significant difference 16. There is agreement between these two studies in this regard.…”
Section: Discussionmentioning
confidence: 53%
“…Overall, cylinder values with autorefraction are significantly overestimated compared with retinoscopy. In a similar comparative study of cycloplegic values using retinoscopy and autorefraction, cylinder values showed a significant difference 16. There is agreement between these two studies in this regard.…”
Section: Discussionmentioning
confidence: 53%
“…The strengths of this review include rigorous methodological procedures to obtain and pool data from 49 789 children. In addition, all the studies in which myopia measurements were self‐reported or measured without cycloplegia were not included in this review due to inaccuracy of these measurements . Several limitations of the present study should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Previous studies evaluating the difference between cycloplegic and non-cycloplegic measurement of refractive error have focused on the use of autorefraction measures in the context of epidemiological classification of refractive error or compared refractive measurement techniques and/or cycloplegic regimes. 1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Outcomes from epidemiological studies using autorefraction for categorisation purposes are not relevant in the context of using retinoscopy to establish refractive error, either as a basis for undertaking a subjective refraction and/or for prescribing spectacles.…”
Section: Introductionmentioning
confidence: 99%